STRATEGI HUMAS UNIVERSITAS MUHAMMADIYAH SURAKARTA DALAM MEMBANGUN BRAND AWARENESS MELALUI KONTEN TIKTOK - Chanara Kaila Haryad; Santoso, Budi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2026)
This study aims to analyze the public relations strategy of Universitas Muhammadiyah Surakarta in building brand awareness through TikTok content. This research employed a descriptive qualitative approach using observation, in-depth interviews, and documentation as data collection techniques. The informants consisted of three members of the UMS Public Relations team and one student as an active audience of the @umsofficialid TikTok account. Data were analyzed through data reduction, data display, and conclusion drawing, supported by source and method triangulation to ensure validity. The findings reveal that the PR strategy emphasizes visual consistency, narrative style, and the integration of educational and entertaining (edutainment) content. Interaction through the comment section reflects the application of adaptive two-way communication aligned with the Excellence Theory principles. TikTok content contributes to strengthening brand recognition and brand recall, shaping UMS’s image as a modern Islamic university that adapts to digital developments. These findings indicate that TikTok functions not merely as a publication tool but as a strategic institutional communication platform in building sustainable brand awareness.